Statuettes and protomes in sacred spaces of Athena, in Gela and Lindos, from the Archaic Period - Ferreira, Felipe Leonardo (Revista do Museu de Arqueologia e Etnologia, 2020)
The purpose of this article is to extend a presentation made at the VI International Week of Archeology - Students - MAE - USP in 2019, as much as possible as suggestions, criticisms and questions raised during a table and the event itself. The formation of the polis was a process that took place throughout the Archaic Period in various movements, articulated to the social transformations of the late Iron Age. A religion was one of the structured elements of many of these nascent communities, being attested to the concentration of offerings in sacred public places that later descended life to the shrines, to the detriment of the immobilization of wealth in tombs, individuals or even collective. From the 8th century BC onwards also realized in materiality certain innovations such as the construction of temples, buildings for the shelter of the image of worship, an abode of god. The Greek expansion movement, which gained great expression in the archaic era with the Support Foundation along the Mediterranean and Black Seas, also contributed to the expansion of the poles in old Greece. The founders took with them a culture and a way of constructing their world material, including their gods, but as specificities of each locality tending to reshape religious practices. In this context, we analyze two types of offerings, terracotta protomes and statues, Sicilian foundations and their metropolises, to try to discern similarities and adaptations that point to possible social or cultural changes in the new communities that are formed.